2023
DOI: 10.1136/bmjopen-2022-067585
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of polypharmacy in pregnancy: a systematic review

Abstract: ObjectivesThe use of medications among pregnant women has been rising over the past few decades but the reporting of polypharmacy has been sporadic. The objective of this review is to identify literature reporting the prevalence of polypharmacy among pregnant women, the prevalence of multimorbidity in women taking multiple medications in pregnancy and associated effects on maternal and offspring outcomes.DesignMEDLINE and Embase were searched from their inception to 14 September 2021 for interventional trials,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 58 publications
(164 reference statements)
0
1
0
Order By: Relevance
“… 14 It is possible that the combined effect of ingredients also might potentiate a harmful effect. 2 A systematic review reported a prevalence of polypharmacy including OTC medications ranging from 4.9% to 38.3%, 26 and an early study of women in Connecticut identified that women who use prescription medications were more likely to use OTC. 27 Significant evidence gaps exist in understanding the teratogenic risk of the vast majority of medications used in early pregnancy, 21 particularly in combination.…”
Section: Discussionmentioning
confidence: 99%
“… 14 It is possible that the combined effect of ingredients also might potentiate a harmful effect. 2 A systematic review reported a prevalence of polypharmacy including OTC medications ranging from 4.9% to 38.3%, 26 and an early study of women in Connecticut identified that women who use prescription medications were more likely to use OTC. 27 Significant evidence gaps exist in understanding the teratogenic risk of the vast majority of medications used in early pregnancy, 21 particularly in combination.…”
Section: Discussionmentioning
confidence: 99%